PREDICTION OF OUTCOME IN PATIENTS WITH SEPSIS USING C-REACTIVE PROTEIN AND APACHE II SCORING SYSTEM (Journal of Pharmaceutical Negative Results, 2023)
Background: One of the most frequent reasons for death in an intensive care unit is sepsis. To evaluate the severity and prognosis of sepsis, a number of clinical grading systems and biochemical indicators have been employed. Objective: To study the outcome of patients with sepsis by using both scoring system (APACHE II) and acute phase reactant (CRP).Methods: 50 patients participated in this prospective trial. At the time of admission, serum CRP and the factors used to determine the APACHE II score were taken. In relation to the severity and course of the disease, the values of CRP concentrations and APACHE II score were compared.Results: Mean CRP value in patients who recovered from the illness was 140.6 mg/dl and mean CRP value in patients who died was 191.1 mg/dl. We observed CRP level of > 137 mg/dl, has sensitivity of 60% and specificity of 60% in predicting mortality in patients with sepsis and was not statistically significant. The mean admission APACHE II score in our patients was 21.4. Mean APACHE II score in patients who died was 24.2, compared to the patients who recovered from the illness was 18.5. The derived predicted mortality estimate was 48% and the actual mortality observed in our study was 26%. The admission APACHE II predicted mortality and the mortality observed in our study group was almost similar. We observed that CRP when compared with APACHE II score <24hrs and from 48-72hrs were both statistically significant with a p value of 0.01 each respectively. When we take both CRP level of > 137 mg/dl and APACHE II score of > 21 to predict the mortality in patients with sepsis, we observed sensitivity 92.85 % and specificity 36.36% in predicting the mortality, which was statistically significant (p 0.01).